Efficacy of antifibrinolytics in pediatric orthopedic surgery: a systematic review and meta-analysis. Issue 1 (January 2020) - Gausden, Elizabeth B.; Brusalis, Christopher M.; Qudsi, Rameez A.; Swarup, Ishaan; Fu, Michael; Dodwell, Emily; Fabricant, Peter D.
Abstract : Antifibrinolytics (AFs) stabilize blood clot formation and reduce bleeding. The purpose of this systematic review and meta-analysis was to determine the impact of AF use on intraoperative blood loss and the need for blood transfusion in pediatric orthopedic surgery. A systematic review was performed using Medline and Embase to identify studies that utilized AFs during pediatric orthopedic surgery. The primary outcome measure was intraoperative blood loss in ml. Secondary outcomes included blood transfusion and thromboembolic events. Pooled estimates were derived from a random-effects model. Heterogeneity was assessed using the Cochrane Q and I 2 statistic. Meta-regression assessed if age or study quality modified the effect of AFs on blood loss. Publication bias was assessed using a funnel plot, Egger regression analysis, and the Kendall τ -test. Twenty studies, with a total of 1356 patients, were included. The mean difference in intraoperative blood loss was 653 ml [95% confidence interval (CI): 464–842 ml, P  < 0.001]. Similarly, the mean difference in percent of blood volume lost was 22% less in patients treated with AFs compared with controls (95% CI: 12–32, P  < 0.001). Patients treated with AFs had a lower odds of transfusion compared to controls (OR: 0.324; 95% CI: 0.105–0.997, P  = 0.049). The use of AF in pediatric orthopedic surgery results in decreased intraoperative blood loss and a lower risk of blood transfusion. The majority of studies included involve spine surgery; the benefits of AFs in extremity surgery in the pediatric population have yet to be delineated. Level of Evidence: Level II. Abstract : Supplemental Digital Content is available in the text.